'Just keep taking them, keep hoping they'll work': A qualitative study of adhering to medications for multimorbidity. Issue 3 (31st October 2021) - Foley, Louise; Hynes, Lisa; Murphy, Andrew W.; Molloy, Gerard J.
Abstract : Objective: Compared to single diseases, health psychology reflects many areas of medical research by affording relatively less attention to the experiences of people self‐managing multiple co‐occurring conditions and, in particular, the experience of managing the associated complex medication regimens. This study aimed to explore the experience of self‐managing multimorbidity among older adults, with a focus on medication adherence. Design: A qualitative approach was taken, using individual semi‐structured interviews. Methods: Sixteen people with complex multimorbidity aged 65 years or older were recruited through general practice to take part in semi‐structured interviews. Data were analysed following guidelines for reflexive thematic analysis. Results: Two themes were generated, with each theme comprising three subthemes. Theme one represents the amplified burden arising from multimorbidity that leads to unique challenges for self‐management, such as integrating multiple medications into daily life, accumulating new symptoms and treatments, and managing evolving medication regimens. Theme two represents pathways towards relief that reduce this burden and promote medication adherence, such as prioritising certain conditions and treatments, resigning to the need for multiple medications, and identifying and utilising adherence supports. Conclusions: We identified factors relevant to medication adherence for older adults with multimorbidity that go beyond single‐disease influences and account for the amplified experience of chronic disease that multimorbidity can produce for some people. While evidence of single‐disease influences remains fundamental to tailoring behavioural interventions to individuals, the impact of multimorbidity on medication adherence should be accounted for in research and practice.